(untitled) (Universal International Scientific Journal, 2026)
This article discusses the impact of globalization processes on the system of higher education and personnel training, issues of increasing the intellectual potential of students and young people, as well as protecting their mental health. The article analyzes the importance of innovative psychological technologies, digital psychohygiene and the development of emotional intelligence in personnel training. It also provides practical recommendations for the formation of stress resistance in future specialists.